Development of a “Turn-on” Fluorescent Probe-Based Sensing System for Hydrogen Sulfide in Liquid and Gas Phase - Bartelmess, Juergen; Valderrey, Virginia; Rurack, Knut (Frontiers in Chemistry, 2019)
A “turn-on” fluorescence sensing system based on a BODIPY-cobaloxime complex for the detection of H2S in liquid and gas phase was developed. To that aim, two cobaloxime complexes bearing an axial pyridyl-BODIPY ligand were initially evaluated as sensitive fluorescent HS− indicators in aqueous solution. The sensing mechanism involves the selective substitution of the BODIPY ligand by the HS− anion at the cobalt center, which is accompanied by a strong fluorescence enhancement. The selection of a complex with an ideal stability and reactivity profile toward HS− relied on the optimal interaction between the cobalt metal-center and two different pyridyl BODIPY ligands. Loading the best performing BODIPY-cobaloxime complex onto a polymeric hydrogel membrane allowed us to study the selectivity of the probe for HS− against different anions and cysteine. Successful detection of H2S by the fluorescent “light-up” membrane was not only accomplished for surface water but could also be demonstrated for relevant H2S concentrations in gas phase.